Pengaruh Pengungkapan Corporate Social Resposibility dan Intellectual Capital terhadap Nilai Perusahaan dengan Kinerja Keuangan sebagai Moderasi - Balit Aplasi, Theresia Sondang; Prihatni, Rida; Nasution, Hafifah (Jurnal Akuntansi, Perpajakan dan Auditing, 2023)
ABSTRACT This study aims to test and analyze the disclosure of Corporate Social Responsibility, Intellectual Capital on firm value with financial performance as moderation. This study uses secondary data sources derived from the company's annual report and sustainability report on non-financial companies on the Indonesia Stock Exchange (IDX) and has used the GRI standard as a guideline for its sustainability report in 2020-2021 with purposive sampling technique. A total final sample of 49 companies was obtained, so that the total observation data during 2020-2022 was 98 data. The analysis technique used is multiple linear regression analysis using SPSS software version 26. The results of this study prove that disclosure of Corporate Social Responsibility, Intellectual Capital has a positive and significant effect on firm value. Financial performance is unable to moderate the effect of Corporate Social Responsibility, but financial performance is able to moderate the effect of Intellectual Capital on firm value. Keywords: Firm Value, CSR Disclosure, Intellectual Capital, Financial Performance.